SELECTION OF LATE BLIGHT RESISTANT VARIETIES IN BANGLADESH FROM CIP POPULATION B3 POTATO CLONES - Mahmud, Abdullah Al (Potato Journal, 2022)
Bangladesh is in a subtropical monsoon region and extends from 20°34’N to 26°38’N latitude, its agriculture iscomprised of several diversified rice-based cropping systems. Potato is an important winter crop across the country. To helpincrease the sustainability of potato production in Bangladesh, a set of medium-term late blight-resistant potato clones bredin CIP were evaluated for diversification potential at six locations from 2008 to 2013. After seven years of field trials, TCRC,BARI identified two clones, namely CIP 393371.58 (coded LB-6) and CIP 393280.64 (LB-7) which are consistently resistant toLate Blight under field conditions without fungicide and yield as well or better than the predominant commercial varieties(Diamant) in a 90-day cropping window. According to the AUDPC, LB-4, LB-5, LB-6 and LB-7 were moderate to highly resistantto Late Blight. The latter two produced over 30 tons of tubers per hectare. Similar yields were recorded in on-farm trials during2011-12. These two clones were entered into regional yield trials as a requirement for variety release by the NSB. Based onfield performance at on-station and farmers’ fields, NSB released BARI Alu-46 (LB-7) in 2013 and BARI Alu-53 (LB-6) in 2014as the country’s two late blight-resistant varieties.